Informal information flows in organizations: The role of the Italian coffee break. Issue 4 (August 2019) - Barmeyer, Christoph; Mayrhofer, Ulrike; Würfl, Konstantin
Highlights: This study focuses on informal information flows in organizations. The role of the coffee break is analyzed in three Italian companies. Eight central functions associated with the coffee break are identified. Informal information flows appear to be essential in Latin cultures. Abstract: Research on information flows within companies has focused on codified formalized information management tools. In practice, it is questionable whether IT-based management systems for storing and disseminating internal information in organizations are sufficiently used by the staff. As an alternative to centralized forms and instruments of information management, there are also informal and dialogic forms, such as the "coffee break" well known in Latin companies: employees come together spontaneously and thus contribute to "natural" internal fluid information circulation. Based on an empirical study conducted in Italian companies, this paper describes essential functions of the coffee break – as a dynamic inter-divisional and heterarchic organizational practice: these include coordination of work processes, confidence building, networking, problem solving, and extension of the meta-knowledge on organizational processes and structures. The paper contributes to the literature on information management by taking into account contextual elements.